Assessing Digital Literacy’s Role in the Adoption of Core Tax Technology: Insights from Indonesia’s Tax System" - Salleh Cahayani Goma, Yohana Babtista Dela; Mahendra, Dominica Devina; Jonathan, Kevin; Suryaatmaja, Kevin (Syntax Literate, 2025)
This study aims to examine the relationship between digital literacy, performance expectancy, effort expectancy, and intention to use tax technology in Indonesia, especially in the implementation of the Core Tax Administration System (CTAS) to be launched by Indonesian tax authority. The study employed a quantitative research design using a purposive sampling technique and collected from 122 respondents, who had Taxpayer Identification Number and used tax technology. The data analysis method used in this research is PLS-based SEM analysis (Partial Least Square). The measurement included four constructs: digital literacy, performance expectancy, effort expectancy, and intention to use technology for tax. All constructs were measured using a five-point Likert scale (1 = strongly disagree, 5 = strongly agree). The results showed that digital literacy has a positive and significant effect on performance expectancy, digital literacy has a positive and significant effect on effort expectancy, performance expectancy has a positive and significant effect on intention to use technology for tax, effort expectancy has no significant effect on intention to use technology for tax, digital literacy has a positive and significant effect on intention to use technology for tax, digital literacy has a positive and significant effect on performance expectancy through intention to use technology for tax, digital literacy has no significant effect on effort expectancy through intention to use technology for tax. Originality/value - Low digital literacy in society is a challenge in the implementation of CTAS, which may affect taxpayers' intention to use this technology.